2016
DOI: 10.1038/ncomms10190
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide screening identifies a KCNIP1 copy number variant as a genetic predictor for atrial fibrillation

Abstract: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia. Previous genome-wide association studies had identified single-nucleotide polymorphisms in several genomic regions to be associated with AF. In human genome, copy number variations (CNVs) are known to contribute to disease susceptibility. Using a genome-wide multistage approach to identify AF susceptibility CNVs, we here show a common 4,470-bp diallelic CNV in the first intron of potassium interacting channel 1 gene (KCNIP1) is strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…The extraction and quantification of mRNA by means of reverse transcription polymerase chain reaction (RT-PCR) were performed as our standard protocols [32]. The RNA was then converted to complementary DNA by reverse transcription with random hexanucleotides and avian myeloblastosis virus reverse transcriptase (Boehringer, Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The extraction and quantification of mRNA by means of reverse transcription polymerase chain reaction (RT-PCR) were performed as our standard protocols [32]. The RNA was then converted to complementary DNA by reverse transcription with random hexanucleotides and avian myeloblastosis virus reverse transcriptase (Boehringer, Mannheim, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…First, the case number of patients with AF and thromboembolic stroke is low in our study. In our previous study [29], we demonstrated that significant disease-associating CNVs could be identified in samples with a case number as low as 100 patients. Nevertheless, our results should be replicated and validated in larger populations and in other ethnic populations.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with its expression pattern, the knockdown of SGOL1 in zebrafish embryos resulted in bradycardia confirming the involvement of SGOL1 in heart rhythm control ( 86 ). KCNIP1 (potassium voltage-gated channel interacting protein 1) is another example of a gene that could be linked by whole genome analysis to heart disease, here atrial fibrillation (AF) ( 82 ). Interestingly, the reported mutation does not lead to a loss of function, but is suggested to increase KCNIP1 levels.…”
Section: Gwa Studies and Functional Genomics In Zebrafish: A Powerfulmentioning
confidence: 99%
“…Interestingly, the reported mutation does not lead to a loss of function, but is suggested to increase KCNIP1 levels. The authors modeled this by the overexpression of KCNIP1 in zebrafish and could show that increased KCNIP1 levels can result in transient atrial tachycardia and AF during high-rate pacing ( 82 ). Norton et al ( 79 ) identified BAG3 (Bcl-2 associated anthanogene 3) as a DCM-associated gene and could confirm its disease relevance by knocking-down BAG3 in zebrafish embryos.…”
Section: Gwa Studies and Functional Genomics In Zebrafish: A Powerfulmentioning
confidence: 99%